Performance Audit of Bio Medical Waste Management in Govt Medical Establishment in Chhattisgarh - CAG of India (CAG of India)
In order to systematize collection, segregation, transportation and disposal of Bio-Medical Waste (BMW), Government of India framed the BMW (Management & Handling) Rules 1998 under the provisions of Environment (Protection) Act, 1986. The Chhattisgarh Environment Conservation Board (CGECB) is responsible for enforcement and monitoring of the provisions of these rules in respect of all health care establishments (HCEs) and to initiate penal action against any contravention. We observed that the State has no mechanism to assess the actual quantum of BMWs generated, collected and disposed. Large numbers of HCEs were operating without valid authorisation for handling of BMWs. CGECB is not aware of the actual number of HCEs in Government and private sectors as well as number of veterinary units in the State. The Department of Veterinary Services has not implemented the BMW Rules at any level. Further, the provision of legal action against the HCEs for not adhering to BMW Rules was also not initiated. The segregation of BMWs was not taking place at any level and wastes were not disposed of as per the BMW guidelines. The State has only one incinerator in operation whereas three incinerators at Korba, Jagdalpur & Kanker remained idle. Even after a lapse of fourteen years since the formation of the State of Chhattisgarh, the implementation of BMW Rules in the State was not effective.